Atypical phenotypes in titinopathies explained by second titin mutations. Issue 2 (24th February 2014) - Evilä, Anni; Vihola, Anna; Sarparanta, Jaakko; Raheem, Olayinka; Palmio, Johanna; Sandell, Satu; Eymard, Bruno; Illa, Isabel; Rojas‐Garcia, Ricard; Hankiewicz, Karolina; Negrão, Luis; Löppönen, Tuija; et al.
<x xml:space="preserve">Abstract</x> Objective Several patients with previously reported titin gene (TTN) mutations causing tibial muscular dystrophy (TMD) have more complex, severe, or unusual phenotypes. This study aimed to clarify the molecular cause of the variant phenotypes in 8 patients of 7 European families. Methods Clinical, histopathological, and muscle imaging data of patients and family members were reanalyzed. The titin protein was analyzed by Western blotting and TTN gene by reverse transcription polymerase chain reaction (RT‐PCR) and Sanger sequencing. Results Western blotting showed more pronounced C‐terminal titin abnormality than expected for heterozygous probands, suggesting the existence of additional TTN mutations. RT‐PCR indicated unequal mRNA expression of the TTN alleles in biopsies of 6 patients, 3 with an limb‐girdle muscular dystrophy type 2J (LGMD2J) phenotype. Novel frameshift mutations were identified in 5 patients. A novel A‐band titin mutation, c.92167C>T (p.P30723S), was found in 1 patient, and 1 Portuguese patient with a severe TMD phenotype proved to be homozygous for the previously reported Iberian TMD mutation. Interpretation The unequal expression levels of TTN transcripts in 5 probands suggested severely reduced expression of the frameshift mutated allele, probably through nonsense‐mediated decay, explaining the more severe phenotypes. The Iberian TMD mutation may cause a more severe TMD rather than LGMD2J when homozygous. The Finnish patient compound heterozygous for the FINmaj TMD mutation and the novel A‐band titin missense mutation showed a phenotype completely different from previously described titinopathies. Our results further expand the complexity of muscular dystrophies caused by TTN mutations and suggest that the coexistence of second mutations may constitute a more common general mechanism explaining phenotype variability. Ann Neurol 2014;75:230–240